The Role of Notary in Resolution of Company's Share Ownership Issues by Two People Based on Act No. 40 of 2007 regarding Limited Liability Companies - Imam Firdaus; Ahmad Khisni; Amin Purnawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Article 88 paragraph (1) of Act No. 40 of 2007 states that RUPS to amend the articles of association can be held if at the meeting at least 2/3 (two thirds) of the total shares with voting rights are present or represented in the RUPS and the decision is valid if it is approved at least 2/3 (two thirds) of the number of votes cast, which causes problems if the Limited Liability Company only has two shareholders with the same percentage of share ownership. The purpose of this study is to determine the impact of Limited Liability Company ownership by two people with the same share percentage and to find out the role of a notary in solving the problem of limited liability company share ownership by two people with the same percentage. The method used in this research is sociological juridical method, the specification in this research is descriptive analytic, the data used are primary data and secondary data, using data collection by interview and literature study, qualitative data analysis, problems analyzed by theory, legal certainty, and Justice Theory. The results of this study indicate that the ownership of PT shares owned by 2 (two) shareholders with balanced share ownership can certainly cause losses to the PT, especially causing difficulties in decision making at the implementation of the AGM. Where if during the RUPS, one of the parties does not approve the results of the RUPS, so the decision cannot be taken because the quorum is not fulfilled. The RUPS is an organ of the Company which has the remaining authority which is not given to the Board of Directors and the Board of Commissioners. The RUPS represents the will of the shareholders as a whole, either as a result of a decision by deliberation or a decision as a result of voting results that are in accordance with and in line with the provisions of the Association and or the Company Law. So it can be said that the RUPS is a meeting held by shareholders in their position as the owner of the company, which has the authority that neither the board of directors nor the board of commissioners have.